当院における気管支鏡の抗酸菌汚染の問題点とその対策 - 雨宮 徳直; 岡藤 和博; 小林 弘明; 村上 眞也; 呉 哲彦; 藤村 政樹 (The Journal of the Japan Society for Respiratory Endoscopy, 2001)
Mycobacterium can be detected from bronchial lavage fluid(BLF) even in patients without any sign of pulmonary tuberculosis or non-tuberculous mycobacteriosis(NTM). Among BLF samples obtained from 460 bronchoscopies performed between January 1997 and September 1998, 13 out of 238 specimens were smear-positive culture-negative(SPCN) for acid-fast bacilli on mycobacterial tests. Nine cases were diagnosed as contamination. We tried to change our method of washing the bronchoscope. First of all, we brushed the inside of the bronchoscope every time before washing it with automatic endoscope washers. The automatic endoscope washers were not used for lower gastrointestinal endoscopes and were sanitized by washing and ultrasonic washing for 2 minutes followed by soaking in 3.5% glutaraldehyde for 10 minutes. In BLF samples obtained from 299 bronchoscopies were performed between February 1999 to January 2000, 4 specimens were positive for acid-fast bacilli and 11 specimens were positive for acid-fast culture out of 198 mycobacterial tests performed. No specimens were SPCN. Four specimens turned out to be contamined by M.gordonae. Next, we further modified the santizing method by exchanging the antiseptic solution for the automatic endoscope washers just before washing the bronchoscope. In BLF samples obtained from 149 bronchoscopies were performed between February 2000 to September 2000, no specimen was positive for acid-fast bacilli and 1 specimen was positive for acid-fast culture out of 123 mycobacterial tests performed. This one positive specimen was diagnosed as NTM(M.Avium) and was not due to contamination. Automatic endoscope washers are widely used to wash and disinfect bronchoscopes. We must take steps to ensure that the automatic endoscope washers do not contaminate bronchoscopes. To avoid contamination, we reached the conclusion that we should exchange the antiseptic solution for the automatic endoscope washer immediately before washing the bronchoscope. 気管支鏡よる気管支洗浄液は, 抗酸菌の汚染を認めることがある。当院において, 1997年1月から1998年9月の期間に気管支洗浄を施行し抗酸菌検査を行った238例のうち, 塗抹陽性培養陰性(smear positive culture negative : SPCN)例が13例存在した。そのうち9例は汚染によるものと考えられた(検討1)。そこで気管支鏡の洗浄法を(1)内視鏡自動洗浄装置による洗浄の前に気管支鏡内のブラシ洗浄を毎回行うこと, (2)自動洗浄装置は下部消化管内視鏡と共用しないこと, (3)流水洗浄1分, 超音波洗浄1分, 3.5%グルタールアルデヒドによる浸漬消毒を10分と規定することに変更して抗酸菌検出状況を検討した(検討2)。1999年2月から2000年1月の期間, 気管支洗浄を行った198例のうち, 塗抹陽性4例, 培養陽性11例であった。SPCNは存在しなかった。4例はM.gordonaeと同定され, 汚染と考えられた。次に自動洗浄装置の消毒液の交換時期を気管支鏡検査の直前に行うように変更して検討した(検討3)。2000年2月から2000年9月の期間, 気管支洗浄を行った123例の内, 塗抹陽性0例, 培養陽性1例であった。培養陽性例は非定型抗酸菌症と判明し, 汚染は存在しなかった。内視鏡自動洗浄装置は気管支鏡の洗浄消毒に広く使用されているが, 抗酸菌汚染に常に注意を払う必要があると考えられる。今回の検討で気管支鏡の洗浄直前に消毒液を交換することが汚染を防ぐのに有効な方法と考えられた。